Oral Health-Related Quality of Life Among Narcotic and Stimulant Users Referred to Maintenance Methadone Therapy Centers in Ahvaz City: Iran - Fatemeh Saki; Maria Cheraghi; Hashem Mohamadian; Fataneh Ghorbanyjavadpour (Frontiers Media S.A., 2022)
IntroductionWe aimed to assess quality of life related to oral health in narcotic or stimulant users those were referred to maintenance methadone therapy (MMT) centers in Ahvaz City, Iran.MethodsIt was a cross-sectional study based on exploratory approach which has conducted on 187 narcotic and stimulant users in Ahvaz city; during 15th May till September 2020. Data was selected by available non-random sampling method. The data collection tools included the demographic variables and the standard OHIP-14 questionnaires. All tests were used as descriptive statistics, Kolmogorov-Smirnov tests, independent t-test, one-way analysis of variance. P-values of less than 0.05 was considered significant.ResultsThe mean and standard deviation of the participants' age was 36.03 ± 8.98 years. The quality-of-life scores related to oral health were totally 34.89 ± 6.50 as well as 37.37 and 33.96 in narcotic and stimulant users, respectively. The total quality of life related to OHIP-14 did not have a significant relationship with variables of age, life companions, level of education, number of children, economic status, employment status, insurance status, underlying disease, toothbrush use status, last dentist visit, and number of missing teeth (P > 0.05). However, a significant difference was found between the quality of life related to oral health based on the type of substance used (narcotic or stimulant), so that the mean quality of life related to oral health was higher in narcotic than stimulant users (P < 0.05).ConclusionQuality of life related to OHIP-14 was more unfavorable in stimulant users than narcotic users. So, policy makers and authorities are required to focus their interventions and research programs to improve health-related quality of life in users, especially stimulant.